Plasticidade de forma de crescimento (arbusto x liana), relações alométricas e padrões de alocação de biomassa em uma espécie invasora - Feitosa, Tiago Soares (2020)
Invasive lianas can negatively affect native species, through mechanical damage, competition for light and space. The adaptive significance of this growth form has been evidenced through interspecific comparative studies between this lianas and other growth forms (trees and shrubs). By using other plants as mechanical support, lianas are able to reduce the biomass allocation of the supporting organs, directing the allocation of this energy to expand the leaf area, lengthen the stem and produce more reproductive organs, in addition to having lower construction costs of stems and leaves. However, a better understanding of the ability to grow as lianas in individuals which are also able to support themselves can provide important information about this growth plasticity. Thus, we seek to understand the adaptive meaning of growth plasticity in invasive species by verifying the hypothesis that the intraspecific variation in the form of growth (shrub or liana) is accompanied by changes in the patterns of biomass allocation in different organs, optimizing other functions due to less demand for support. For this, we studied the species Cryptostegia madagascariensis Bojer Ex Decne, an invader in the northeast region of Brazil that occurs as isolated shrubs in open areas and as lianas when populations attain high densities with support availability. Fifteen individuals with support and 15 isolated were collected at a permanent monitoring site in the municipality of Jaguaruana, Ceará, Brazil. The selected individuals were measured for height (H) and basal diameter (D). Five leaves and three stem pieces were separated for analysis of leaf area (LA) and wood density (WD). The collected plants were fractionated in stem, leaves and fruits and the biomass of each fraction was weighed after drying. With the leaves previously colected, measurements of LA, specific leaf area (SLA) and leaf area ratio (LAR) were made. No changes were found in the patterns of biomass allocation of stem and leaf between growth forms. However, the relationship of fruit fraction to above ground biomass (ABG) varied between forms: isolated individuals in a smaller size have higher fruit biomass, but this difference was lost at larger sizes. WD, SLA and LAR also did not differ between liana and shrubs, indicating similar construction costs for these organs between growth forms.Despite these similarities, individuals with support (liana) showed higher H and AGB than isolated ones with the same basal diameter. This result indicates changes in the allometric relationships of H and AGB between supported and isolated individuals, which may have implications for intraspecific competition for resources and intrapopulation regulation. We concluded that the intraspecific allocation patterns did not follow the variation in the form of growth. However, the larger sizes (height and biomass) achieved in the presence of support can be a characteristic that contributes to the competitive performance and invasion success.